2012
DOI: 10.1371/journal.pone.0050884
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Axis Niche Examination of Ecological Specialization: Responses to Heat, Desiccation and Starvation Stress in Two Species of Pit-Building Antlions

Abstract: Classical ecological studies discussing specialization usually focus on species’ performance along one niche axis. This approach may overlook niche differentiation evident in another dimension which could explain species co-occurrence. The present research exemplifies a comprehensive approach to examining local adaptation. Specifically, we examined multiple niche axes by subjecting a model organism to various experimental conditions to monitor responses to extreme stress associated with heat, desiccation and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 68 publications
1
13
0
1
Order By: Relevance
“…The results of our experiment show that higher soil temperatures resulted in more frequent trap building and traps with a larger diameter and volume. These findings are consistent with those from some earlier studies on trap building in antlion larvae (Kitching 1984 ; Arnett and Gotelli 2001 ; Klokočovnik et al 2016 ), but they contrast with the conclusions of other studies showing either no clear effects of temperature on trap volume (Rotkopf et al 2012 ) or negative effects of temperature on trap-building frequency (Klein 1982 ). Our findings do not support hypothesis 2, which predicts that antlion larvae challenged by cooler conditions might compensate for their reduced behavioral capacity to immobilize prey and prevent rescue by ant nest-mates by maintaining larger traps.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of our experiment show that higher soil temperatures resulted in more frequent trap building and traps with a larger diameter and volume. These findings are consistent with those from some earlier studies on trap building in antlion larvae (Kitching 1984 ; Arnett and Gotelli 2001 ; Klokočovnik et al 2016 ), but they contrast with the conclusions of other studies showing either no clear effects of temperature on trap volume (Rotkopf et al 2012 ) or negative effects of temperature on trap-building frequency (Klein 1982 ). Our findings do not support hypothesis 2, which predicts that antlion larvae challenged by cooler conditions might compensate for their reduced behavioral capacity to immobilize prey and prevent rescue by ant nest-mates by maintaining larger traps.…”
Section: Discussionsupporting
confidence: 91%
“…Given that antlion larvae can rapidly re-establish their traps, even a brief change in environmental temperatures occurring over days or weeks may significantly alter the pressure of antlion larvae on prey of different sizes. Indeed, Rotkopf et al ( 2012 ) demonstrated that the brief exposure of M. hyalinus and C. lineosa larvae to elevated temperatures resulted in the enlargement of traps and ultimately increased the speed of prey capture (although the authors did not directly investigate the effects of trap enlargement on the ability to capture larger prey). Overall, we conclude that measurement of the ecological impacts of antlion larvae on natural communities should not ignore their hunting capacities that strongly depend on the thermal environment and larval size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal tolerance of pit-building predators has been rarely studied. Two exceptions studied the thermal activity range of an antlion and its common ant prey ( Marsh 1987 ) and another one demonstrated that antlions of shaded habitats have lower heat tolerance than those of sun-exposed habitats ( Rotkopf et al. 2012 ).…”
Section: Methodsmentioning
confidence: 99%